On the Emergence and Awareness of Auditory Objects - Shamma, Shihab (Public Library of Science, 2008)
How do humans successfully navigate the sounds of music and the voice of a friend in the midst of a noisy cocktail party? Two recent articles inPLoS Biology provide psychoacoustic and neuronal clues about where to search for the answers.